Kajian Permukiman Kumuh Tepian Sungai Ditinjau Dari Karakter Spasial Kawasan (Kelurahan Gandus Palembang) - Fuji Amalia; Listen Prima; Rizka Drastiani; Sri Lilianti Komariah (Program Studi Arsitektur Fakultas Teknik Universitas Sriwijaya, 2023)
Riverside settlements are a characteristic of the city of Palembang. Residential in Palembang City are increasing and growing every year while the availability of residential land is relatively constant, giving rise to dense and slum settlements. Most of the settlements located along the Musi River can be categorized as densely populated settlements with various problems in them. Gandus Sub-District is one of the sub-districts in Palembang City which is located in a strategic area which has riverside settlements that are close to the Musi Bridge 2. The Gandus area is included in the category of slum areas which has resulted in a decrease in the environmental quality of the area. This study aims to examine the problems of slum settlements in terms of the spatial character of space. This qualitative method was carried out to identify the spatial physical conditions of the Gandus settlement relying on field observation surveys, which were compiled with a descriptive analysis of the physical spatial settlements as a solution to slum problems in the Gandus settlement along the river. buildings, pedestrian circulation that is continuous but interrupted at the end of the river, lack of open space arrangement so that it becomes a place for wild plants to grow, and lack of supporting elements for activities. Therefore, elements such as land use, buildings, pedestrian circulation, open space and activity support can be elements that can improve environmental quality if properly managed. Then, the result of the research would be a significant input for the development program in the area.